Family Responsibilities and Silence of Rural Migrant Workers in China: The Role of Town-Fellow Organizations - Yuan, Fang; Cooke, Fang Lee; Zhong, Teng; An, Fansuo (Relations industrielles / Industrial Relations, 2021)
Employee voice in China remains an under-researched topic from an industrial relations perspective. We investigated the relationship between family dependents (children and elderly) and migrant worker silence, with town-fellow organizations as a moderator, based on the data of the 2014 Guangdong Migrant Workers Survey. The findings reveal that migrant workers with dependent children are more likely to keep silent when their labour rights and interests are violated at the workplace, while family responsibilities for dependent elderly family members do not have significant impacts on migrant workers’ silence. In addition, town-fellow organizations weaken the association between family responsibilities for elderly dependents and silence. Our study contributes to the existing literature on employee voice and provides evidence on the role of town-fellow organizations in China as an informal, emerging institutional actor that regulates labour relations through their involvement in dispute resolution.